9: PROCESSES OF TECTONISM, MAGMATISM AND MINERALIZATION: LESSONS FROM EUROPE - Blundell D.; Arndt N.; Cobbold P.R.; Heinrich C. (My University, 2005)
Metallogenic provinces in Europe range in age from the Archaean to the Neogene. Deposit types include porphyry copper and epithermal Cu–Au, volcanic-hosted massive sulphide (VMS), orogenic gold, Fe-oxide–Cu–Au, anorthosite Fe–Ti-oxide and sediment-hosted base-metal deposits. Most of them formed during short-lived magmatic events in a wide range of tectonic settings; many can be related to specific tectonic processes such as subduction, hinge retreat, accretion of island arcs, continental collision, lithosphere delamination or slab tear. In contrast, most sediment-hosted deposits in Europe evolved in extensional, continental settings over significant periods of time. In Europe, as elsewhere, ore formation is an integral part of the geodynamic evolution of the Earth's crust and mantle. Many tectonic settings create conditions conducive to the generation of water-rich magma, but the generation of ore deposits appears to be restricted to locations and short periods of change in temperature and stress, imposed by transitory plate motions. Crustal influence is evident in the strong structural controls on the location and morphology of many ore deposits in Europe. Crustal-scale fault–fracture systems, many involving strike-slip elements, have provided the fabric for major plumbing systems. Rapid uplift, as in metamorphic core complexes, and hydraulic fracturing can generate or focus magmatic–hydrothermal fluid flow that may be active for time spans significantly less than a million years. Once a hydrologically stable flow is established, ore formation is strongly dependent on the steep temperature and pressure gradients experienced by the fluid, particularly within the upper crust. In Europe, significant fracture porosity deep in the crystalline basement (∼1%) is not only important for magmatic–hydrothermal systems, but allows brines to circulate down through sedimentary basins and then episodically upward, expelled seismically to produce sediment-hosted base-metal deposits and Kupferschiefer copper deposits. Emerging research, stimulated by GEODE, can improve the predicting power of numerical simulations of ore-forming processes and help discover the presence of orebodies beneath barren overburden.
Keywords: Geodynamic processes; Structural controls; Magmatic–hydrothermal systems; Ore formation